THE CLASSIFICATION OF ENGLISH CONSONANTS - Teshaboyeva Nafisa Zubaydulla qizi; Qodirova Iroda Ulugbek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides a comprehensive overview of the classification of English consonants, which are pivotal in shaping the sounds of the language. It categorizes consonants based on three primary criteria: voicing, place of articulation, and manner of articulation. This detailed explanation serves to inform readers about the complexities of consonant sounds in English, promoting a deeper engagement with the study of phonetics and linguistics.